Analisa Teknik dan Permodelan Penentuan Sisa Umur Transformator 20 KV Berdasarkan Profil Beban Lebih pada Jaringan Distribusi - Ahmad Taufiqul Lubab (LPPM Institut Pendidikan Nusantara Global, 2026)
Excessive or continuous loading above 80% in distribution transformers leads to elevated hot-spot temperatures, accelerated insulation degradation, and a reduced service life. Under standard design assumptions, distribution transformers have an expected operational lifespan of approximately 30 years. At PLN ULP Sumba Jaya, three transformer units (A, B, and C) operate at loading levels exceeding 80%. A modeling-based approach is employed to mitigate accelerated aging and to enhance reliability and asset management in the distribution network. Three distribution transformers (A, B, and C), each rated at 100 kVA, were operated on the same feeder. The implemented modeling approach predicts load growth and the associated loss of life. Transformer A exhibits a relative loss of life of 19.87%, corresponding to an aging rate of 4.77 hours per day and an estimated remaining lifetime of 13.22 years. Transformer B shows a higher relative loss of life of 24.29%, with a daily aging rate of 5.83 hours, resulting in a remaining lifetime of 11.36 years. Transformer C experiences a relative loss of life of 14.39%, equivalent to 3.45 aging hours per day, and retains an estimated remaining lifetime of 15.13 years. The results indicate that sustained overloading accelerates transformer aging, while the use of data-driven modeling enables faster and more effective estimation of the remaining service life without reliance on complex and costly direct testing, thereby supporting timely maintenance actions such as load balancing or the installation of additional distribution substations to extend the transformer’s operational lifetime.